Independent association between subjective cognitive decline and frailty in the elderly. - Tsung-Jen Hsieh; Hsing-Yi Chang; I-Chien Wu; Chu-Chih Chen; Hui-Ju Tsai; Yen-Feng Chiu; Shu-Chun Chuang; Chao A Hsiung; Chih-Cheng Hsu (PLoS ONE)
Background The relationship between subjective cognitive decline and frailty, two components of the so-called reversible cognitive frailty, in the elderly remains unclear. This study aims to elucidate whether this association exists, independent of confounding factors such as nutritional status, kidney function, inflammation, and insulin resistance. Methods 2386 participants (≥ 65 years of age) selected from the Healthy Aging Longitudinal Study in Taiwan (HALST) study. Fried frailty phenotype was adopted to quantify frailty status. We classified cognitive status into two categories-subjective cognitive decline (SCD), and normal cognition-and used polytomous logistic regressions to investigate the associations between SCD and frailty. Results There were 188 (7.88%), 1228 (51.47%), and 970 (40.65%) participants with frailty, pre-frailty, and robustness, respectively. Compared to those with normal cognition, elders with SCD were more likely to have pre-frailty (odds ratio [OR]: 1.36, 95% confidence interval [CI]: 1.10-1.67, p = 0.004) or frailty (OR: 1.78, 95% CI: 1.23-2.58, p = 0.002) after adjusting for age, gender, education level, comorbidity, nutritional status, kidney function, and biochemical-related factors. Conclusions A significant association between subjective cognitive decline and frailty was revealed in this study. Subjective cognitive decline was positively associated with pre-frailty or frailty even after adjusting for potential confounding factors. Our results can provide useful references in understanding mechanisms and developing suitable preventive strategies for the elderly with reversible cognitive frailty.